Fast fault location scheme for distribution systems based on fault transients - Aboshady, F.M.; Thomas, David W.P.; Sumner, M. (2017)
This paper presents a combined double-end and single-end fault locator for distribution systems. The technique lies under the impedance based category and uses the fault generated high frequency components to locate the faults. The combination of double-end and single-end allows the method to discriminate between faults on the main feeder and those on laterals. Also, the method only requires a short data window as it depends on the high frequency components. The evaluation of the method considers different system and fault parameters e.g. loading taps, loading unbalance, fault type and fault resistance. To validate the proposed technique, the IEEE 34 nodes system is used to simulate different test cases.